Online sexual harassment and negative mood in Croatian female adolescents - Mitchell, Kirstin (Eur Child Adolesc Psychiatry, 2020)
Online sexual harassment (OSH) appears to be a relatively frequent phenomenon, particularly for older adolescents. It is also a gendered experience. Compared to their male peers, female adolescents are more likely to experience OSH and find it upsetting. This study sought to explore the role of resilience in explaining the association between online sexual harassment (OSH) and negative mood (i.e., depression and anxiety symptoms) among female adolescents. Using data from a panel sample of 477 female Croatian adolescents (age at baseline = 15.8 years; SD = 0.48) and two-wave cross-lagged path analysis, we investigated OSH, changes in depression/anxiety symptoms, association between OSH and negative mood, and the role of resilience. During the 26-month period under observation, OSH and negative mood were associated cross-sectionally, but not longitudinally. This suggests the negative mood effects of OSH exposure may be short-lived or that factors other than OSH explain changes in negative mood over time. Resilience was consistently and negatively associated with negative mood, but not OSH. In adolescent girls with low levels of resilience, OSH was associated with negative mood; no such relationship was observed among their highly resilient peers. Experiences other than OSH appear to be more pertinent in predicting symptoms of negative mood in older adolescent girls over time. Given that resilience attenuated the relationship between OSH and negative mood, efforts to increase resilience to online challenges may be more helpful than efforts to limit or control young people’s online exposure.